2020
DOI: 10.1111/1748-5967.12491
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and severity of mite Polyphagotarsonemus latus (Tarsonemidae) on chili plants: Analysis of pest‐weather and host plant characteristics

Abstract: The abundance, infestation, and severity of the mite Polyphagotarsonemus latus were studied on the chili (Capsicum frutescens L., Solanaceae) varieties BARI Morich 1, BARI Morich 2, BARI Morich 3, BINA Morich 1, and Bogura Morich from November 2017 to June 2018. The abundance of mites was found from 05 February to 28 May, and the peak abundance on the chili varieties occurred on 09 April. Mite population showed the highest and the lowest occurrences on BINA Morich 1 and BARI Morich 2, respectively. The abundan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
0
6
1
Order By: Relevance
“…Although the frequency of mite attacks did not correlate with plant height in several studies (Borah,1987;Hosamani, 2007;Nasrin, et al 2021), current results showed a positive and significant correlation between plant height and mite attack. Pest attacks can affect the plant height in different crops.…”
Section: Resultscontrasting
confidence: 87%
See 4 more Smart Citations
“…Although the frequency of mite attacks did not correlate with plant height in several studies (Borah,1987;Hosamani, 2007;Nasrin, et al 2021), current results showed a positive and significant correlation between plant height and mite attack. Pest attacks can affect the plant height in different crops.…”
Section: Resultscontrasting
confidence: 87%
“…In another study in Bangladesh, the peak of the mite was recorded in the second week of April (Nasrin et al, 2021). The development and reproduction of mites depend on the temperature and rainfall pattern (Gotosh et al, 2014).…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations